Therapeutic Basis of Clinical Pain Modulation. Issue 6 (11th May 2015) - Kirkpatrick, Daniel R.; McEntire, Dan M.; Hambsch, Zakary J.; Kerfeld, Mitchell J.; Smith, Tyler A.; Reisbig, Mark D.; Youngblood, Charles F.; Agrawal, Devendra K.
Abstract: Pain is a hallmark of almost all bodily ailments and can be modulated by agents, including analgesics and anesthetics that suppress pain signals in the central nervous system. Defects in the modulatory systems, including the endogenous pain‐inhibitory pathways, are a major factor in the initiation and chronicity of pain. Thus, pain modulation is particularly applicable to the practice of medicine. This review summarizes the existing literature on pain modulation. Here, we critically reviewed the literature from PubMed on pain modulation published primarily within the past 5 years in high impact journals. Specifically, we have discussed important anatomical landmarks of pain modulation and outlined the endogenous networks and underlying mechanisms of clinically relevant pain modulatory methods. The Gate Control Theory is briefly presented with discussion on the capacity of pain modulation to cause both hyper‐ and hypoalgesia. An emphasis has been given to highlight key areas in pain research that, because of unanswered questions or therapeutic potential, merit additional scientific scrutiny. The information presented in this paper would be helpful in developing novel therapies, metrics, and interventions for improved patient management.